Effects of the supplemental chromium form on performance and metabolic profile in laying hens exposed to heat stress - Şahin, Nurhan; Hayirli, A.; Orhan, C.; Tuzcu, M.; Komorowski, J. R.; Şahin, Kazım (Oxford Univ Press, 2018)
This experiment was conducted to compare the effect of the supplemental chromium (Cr) form on performance, egg quality, and metabolic profile in laying hens exposed to heat stress (HS). Laying hens (n = 1800; 16-wk-old; Lohmann LSL-Lite) were kept in cages in temperature-controlled rooms at either 22 +/- 2 degrees C for 24 h/d (thermoneutral, TN) or 34 +/- 2 degrees C for 8 h/d, from 08: 00 to 17: 00 h, followed by 22 degrees C for 16 h (HS) for 12 wks. Hens reared under both environmental conditions were fed 1 of 3 diets: a basal diet and the basal diet supplemented with either 1.600 mg of chromium-picolinate (CrPic, 12.43% Cr) or 0.788 mg of chromium-histidinate (CrHis, 25.22% Cr) per kg of diet, delivering 200 mu g elemental Cr per kg diet. Data were analyzed by 2-way ANOVA. Exposure to HS caused decreases in feed intake (P < 0.0001), egg production (P < 0.0001), egg weight (P < 0.0001), eggshell weight (P < 0.0009), eggshell thickness (P < 0.0001), eggshell strength (P < 0.0001), and Haugh unit (P < 0.0001), deterioration in feed conversion ratio (P < 0.0001), increases in serum glucose and cholesterol concentrations (P < 0.0001 for both), decreases in serum and egg yolk Cr concentrations (P < 0.0001 for both), and decreases in serum Na (P < 0.002) and K (P < 0.01) concentrations. Both Cr sources were equally effective in alleviating performance variables under the HS condition. However, neither Cr sources alleviated deteriorations in egg quality parameters and serum electrolytes. Both Cr sources decreased serum glucose and cholesterol concentrations and increased serum and egg yolk Cr concentrations under the HS condition. In conclusion, HS adversely affected laying performance, egg quality, and metabolic profile. Both CrPic and CrHis partially alleviated the adverse effect of HS on these parameters. Inclusion of either Cr source could be a part of nutritional management strategies to overcome the adverse effects of HS performance and metabolic profile in laying hens.
Keywords: chromium-histidinate; chromium-picolinate; heat stress; laying hen